Baru Pulp (Dipteryx alata Vogel): Fruit from the Brazilian Savanna Protects against Oxidative Stress and Increases the Life Expectancy of Caenorhabditis elegans via SOD-3 and DAF-16 - Natasha Rios Leite; Laura Costa Alves de Araújo; Paola dos Santos da Rocha; Danielle Araujo Agarrayua; Daiana Silva Ávila; Carlos Alexandre Carollo; Denise Brentan Silva; Leticia Miranda Estevinho; Kely de Picoli Souza; Edson Lucas dos Santos (Biomolecules, 2020)
Fruits are sources of bioactive compounds that are responsible for several biological activities. Therefore, this study aimed to identify the chemical composition of the pulp of the Brazilian Savanna fruit Dipteryx alata; evaluate its toxic effects, influence on the life expectancy of the nematode Caenorhabditis elegans, and its antioxidant activities in vitro and in vivo; and describe the mechanisms involved. The chemical compounds identified include phenols, terpenes, fatty acid derivatives, vitamins, and a carboxylic acid. The in vitro antioxidant activity was demonstrated by radical scavenging methods. in vivo, the D. alata fruit pulp was not toxic and promoted resistance to oxidative stress in nematodes exposed to a chemical oxidizing agent. Furthermore, it promoted an increased life expectancy in wild-type nematodes and increased the expression of superoxide dismutase and the nuclear translocation of DAF-16. These results suggest that the beneficial effects identified are related to these two genes, which are involved in the regulation of metabolic activities, the control of oxidative stress, and the lifespan of C. elegans. These beneficial effects, which may be related to its chemical constituents, demonstrate its potential use as a functional and/or nutraceutical food.